Germany : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2001)
The German economy has been experiencing as many setbacks as achievements. Continued wage moderation will be essential to aid recovery. Macroeconomic policies are limited by euro area constraints and the sizable public debt burden. Expenditure restraint is the cornerstone of the fiscal adjustment strategy. Labor market rigidities have proved the most intractable structural problem. Germany's record on product market liberalization is favorable and the reform momentum should be kept up. The quality of Germany's statistics is more than adequate for the purpose of effective surveillance.